Thematic Eksplorative Democratic Learning: Suatu Eksplorasi Konsep Energi di Pulau Para Kabupaten Kepulauan Sangihe - Fabian Tamara; Patricia M. Silangen; Alfrie M. Rampengan; Jeane V. Tumangkeng (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2024)
This research aims to describe the results of exploratory learning about objects in the form of energy concepts on Para Island. The main research activities are exploring objects (Sun, ocean currents, sea waves, and wind), as well as scientific concepts and processes using the Thematic Exploration Learning in Democratic Interaction (HOTL-DI) type A model. Research at Tatoereng State Middle School Classes VII-VIII from June to July 2021. Exploration activities were carried out in three stages. The first stage is material exploration (objects, concepts, and scientific processes), carried out by the research team facilitated by the Pamong Teacher. The second stage is learning activities regarding energy concepts by class VII-VIII students. The results of the phase II assessment are used as a reference for going directly to the field to conduct exploration. Phase III exploration activities for target groups facilitated by mentors and researchers. The research results showed that at the beginning of the activity, all students experienced difficulties, but later, they developed the initiative to carry out their exploration. The exploration results show the development of the concept in the exploration step. Most students experienced improvement in identifying concepts and constructing a comprehensive network of energy concepts.